An unexpected knock on Corrigan’s secret door - Woywodt, Alexander (NDT Plus, 2010)
Corrigan’s secret door describes a metaphorical escape route for busy physicians. The term was derived from the successful and exceptionally busy professional life of Irish physician Dominic John Corrigan (1802–80). It is claimed that Corrigan’s outpatient clinic was so busy that he required a secret door in his consulting rooms to escape from the ever-growing queue of eager patients. The origins of this charming story are unknown, and the door may have never existed. However, at present, Corrigan’s secret door is often quoted when busy physicians have their own little ways in surviving a stressful professional life. Generations of British-trained doctors have grown up with Corrigan’s secret door, as it was featured in the introduction of the Oxford Handbook of Clinical Medicine. Accordingly, trainees as well as more senior doctors are often reminded that having a ‘secret door’ is vital in surviving in the medical profession. My own escape is through classical music and the violoncello, in particular. As the name implies, my own secret door is normally invisible to colleagues and patients. This little article is about a patient who found me out, and a reflection on the role of classical music and the cello in my professional life.